Automata Theory and Formal Languages. - Kandar, Shyamalendu (2012)
The organized and accessible format of Automata Theory and Formal Languages allows students to learn important concepts in an easy-to-understand, question-and-answer format. This portable learning tool has been designed as one-stop references for students to understand and master the subjects by themselves.
4.5 Equivalence of Two Finite Automata and Two Regular Expressions -- 4.6 Construction of Regular Grammar from a Regular Expression -- 4.7 Pumping Lemma and its Application -- 4.8 Closure Properties of Regular Set -- What We Have Learned So Far -- Solved Problems -- Multiple Choice Questions -- Exercises -- Fill in the Blanks -- Answers -- Chapter 5: Context Free Grammar -- 5.1 Context Free Grammar: Definition and Examples -- 5.2 Derivation and Parse Tree -- 5.3 Ambiguity -- 5.4 Left Recursion and Left Factoring -- 5.5 Simplification of CFG -- 5.6 Normal Form -- 5.7 Constructing FA from Regular Grammar -- 5.8 Closure Properties of CFL -- 5.9 Pumping Lemma for CFL -- 5.10 Ogden's Lemma for CFL -- 5.11 Decision Algorithms -- What We Have Learned So Far -- Solved Problems -- Multiple Choice Questions -- Exercises -- Fill in the Blanks -- Answer -- Chapter 6: Pushdown Automata -- 6.1 Basics of Pushdown Automata -- 6.2 Acceptance by a PDA -- 6.3 Examples -- 6.4 Deterministic PDA and Non-Deterministic PDA -- 6.5 Pushdown Automata from Context Free Grammar -- 6.6 Graphical Notation for PDA -- What We Have Learned So Far -- Solved Problems -- Multiple Choice Questions -- Exercises -- Fill in the Blanks -- Answers -- Chapter 7: Turing Machine -- 7.1 Basic of Turing Machine -- 7.2 Examples -- 7.3 Transitional Representation of Turing Machine -- What We Have Learned so Far -- Solved Problems -- Multiple Choice Questions -- Exercises -- Fill in the Blanks -- Answers -- References -- Index.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2018. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books